(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The question asked by Socrates in Plato’s Eutyphro: ’Is the pious dear to the gods because it is pious, or is it pious because it is dear to the gods?’ can be understood as symbol of a growing tension between religion and philosophy (faith and reason). Additionally, this question is linked to a crucial issue of morality’s foundations because a question ‘what is pious?’ can be interpretated as a question ‘what is morally right?’ in particular religion. Socrates’ question about the meaning of piety not only is important itself but also because of its reason and consequences. It represents the beginning of the process that lead to conclusion that only reason can decide what is pious. This conclusion is an essential feature of the Western thought because it was underlying philosophical theology evolving since Antiquity and natural religion born in Modern Age. The platonic paradigma that only the Good can be divine is applied to both of them. The question I raised in my article has ancient origin. Nevertheless, it is universal and transhistorical question, important for Modern World.